A piezoelectric based energy harvester with magnetic interactions: modelling and simulation - Ibrahim , Dauda Sh.; Abdul Muthalif, Asan Gani; Saleh, Tanveer (Trans Tech Publications, Switzerland, 2015)
In recent years, utilizing kinetic energy in mechanical vibrations has become an interesting area of research. This is due to ubiquitous sources of vibration energy, coupled with the ever increasing demands to power wireless sensing electronics and Microelectromechanical (MEMs) devices with low energy requirements. Thus, researchers have ventured into developing different system configurations with the aim of harvesting vibration energy to power these devices. Cantilever beam systems with piezoelectric layer have been used as vibration energy scavengers due to their abilities of converting kinetic energy in vibrating bodies into electrical energy, whereas permanent magnets have been used to improve their performance. The only unresolved challenge is to develop energy harvesters that can produce optimum energy at a wider bandwidth. In this study, a mathematical model of a system of cantilever beams with piezoelectric layers having a magnetic coupled tip mass is proposed. The lumped parameter model of the harvester is developed to estimate the power output of the proposed harvester, and to visualise the effect of magnetic coupled tip mass in widening the frequency bandwidth of the energy harvester. Preliminary Simulation results using MATLAB have however shown the effectiveness of the proposed system.